Dicrocoelium Dendriticum Infection in a Patient with Crohn’s Disease - Franzjosef Schweiger; Magdalena Kuhn (Canadian Journal of Gastroenterology)
Infection with Dicrocoelium dendriticum in humans is rarely reported in the medical literature. This liver fluke, which commonly infects ruminants, has a complex life cycle with two intermediate hosts – the land snail and the ant. True human infection occurs by ingestion of the second intermediate host, but spurious infections have occurred after consumption of undercooked animal liver. The present report describes a patient with active Crohn’s disease whose stool contained D dendriticum eggs. A brief discussion of the medical literature is presented.